A systemic functional linguistic investigation into experiential meanings of PETA online news reports / Ooi Zao May - Ooi, Zao May (2017)
The current Systemic Functional Linguistic (SFL) study is an investigation into experiential meanings related to the portrayal of animal cruelty in PETA (People for the Ethical Treatment of Animals) online news reports, a kind of animal rights literature. Halliday’s System of Transitivity is used as the theoretical framework. Previous linguistic studies on transitivity have covered different genres like political speeches, literary texts, postcolonial texts, narrative religious texts and medical texts among many others. However, there is a scarcity of transitivity analyses on online news reports from a Systemic Functional Linguistic (SFL) point of view. Hence, the current study fulfills the gap in research. Particularly data on the portrayal of cruelty meted out to animals in facilities where they are held captive is examined. A gloss of the contents in the data shows six prominent themes which are “cruel treatment,” “humane reactions,” “intervention,” “wrongdoing,” “call-to-action” and “negative environment.” The transitivity analysis shows that material process (50.83%; n = 92) is the predominant Process, followed by relational (20.44%; n = 37), verbal (12.71%; n = 23) and behavioral (8.84%; n = 16) processes. The material processes are used to express mostly the theme “cruel treatment” (45.65%) while the relational processes are used to express mostly the theme “humane reactions” (43.24%). The fields of social activity corresponding to the different Processes are identified and related to the various themes. The current study is significant for enhancing our understanding of transitivity and experiential meanings arising from the fields of social activity shown in PETA online news reports which may be of use to animal rights activists, animal lovers, language practitioners and those interested in a career on writing for online news.